2015
DOI: 10.1080/02702711.2015.1072608
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Perceptions Affect Boys’ and Girls’ Reading Motivation Differently

Abstract: The aim of this study was to examine the relationship between teacher perceptions and children's reading motivation, with specific attention to gender differences. The reading self-concept, task value, and attitude of 160 fifth and sixth graders were measured. Teachers rated each student's reading comprehension. Results showed that for boys, teacher expectations had no influence on the three constructs of reading motivation measured, whereas for girls, teacher expectations did predict reading self-concept and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 72 publications
1
18
0
3
Order By: Relevance
“…In line with previous studies (Boerma et al, 2016;Gilbert et al, 2014;Urhahne, 2015;Wentzel et al, 2010;Woolley et al, 2010;Zhu et al, 2018), we expected that teacher expectations would be associated with students' motivation and behavioural engagement. We expected that this relation would be partly or fully mediated by need-supportive teaching.…”
Section: Present Studysupporting
confidence: 83%
See 1 more Smart Citation
“…In line with previous studies (Boerma et al, 2016;Gilbert et al, 2014;Urhahne, 2015;Wentzel et al, 2010;Woolley et al, 2010;Zhu et al, 2018), we expected that teacher expectations would be associated with students' motivation and behavioural engagement. We expected that this relation would be partly or fully mediated by need-supportive teaching.…”
Section: Present Studysupporting
confidence: 83%
“…In this vein, Urhahne (2015) suggests that through their behaviours, teachers communicate their expectations to students, which in turn affects students' motivation and thereby their achievement outcomes (see also , Brophy, 1983). Although research on the relations between teacher expectations and student motivation is rather scarce, several studies have found that more positive teacher expectations are associated with higher levels of motivation (Boerma, Mol, & Jolles, 2016;Gilbert et al, 2014;Urhahne, 2015;Wentzel, Battle, Russell, & Looney, 2010;Woolley, Strutchens, Gilbert, & Martin, 2010). Further, a wide array of previous research has indicated that intrinsic motivation can affect students' achievement outcomes (e.g., Baker, 2003;Cerasoli, Nicklin, & Ford, 2014;Guay, Ratelle, Roy, & Litalien, 2010;Taylor et al, 2014).…”
Section: Teacher Expectationsmentioning
confidence: 99%
“…In contrast, when a teacher's expectations are low, students' results tend to be poorer (Rubie-Davies, Peterson, Sibley & Rosenthal, 2015;Rubie-Davies & Rosenthal, 2016). To date, the consensus has been that teacher expectations may be biased by student gender (Boerma, Mol, & Jolles, 2015;Tiedemann, 2000) and socio-economic status (SES) (Auwarter & Aruguete, 2008;Del Río & Balladares, 2010;Regalla, 2013;Sweatt, 2000;van den Bergh, Denessen, Hornstra, Voeten, & Holland, 2010).…”
Section: Palabras Clavementioning
confidence: 99%
“…Teacher expectations have been studied primarily in countries such as New Zealand (Rubie-Davies, Hattie, & Hamilton, 2006;Speybroeck et al, 2012), the USA (Boerma et al, 2015;Sorhagen, 2013), and Germany (Tiedemann, 2000). However, in less-developed countries, such as those in Latin America, the subject has not been researched in any depth.…”
Section: Palabras Clavementioning
confidence: 99%
“…Affective dimension, which has an effective role in the variables (Putman and Walker, 2010), includes some variables such as anxiety, attitude, motivation, interest, self-efficacy, and metacognitive reading strategies. (Lawrence, 2007;McGeown, Osborne, Warhurst, Norgate, Duncan, 2016;Boerma, Mol and Jolles, 2016;Kelley, Siwatu, Tost and Martinez, 2015; Huang ve Yang, 2015; Lin, Wong and McBrideChang, 2012;Becker, McElvany and Kortenbruck, 2010;Balcı, 2009). These variables influence each other in various dimensions, as well as interacting with each other.…”
mentioning
confidence: 99%